PRODUCTION OF ALPHA-L-ASPARTYL-L-PHENYLALANINE METHYL ESTER - KIRA IKUO; YOKOZEKI KENZO; ASANO YASUHISA (1998)
PROBLEM TO BE SOLVED: To provide a method for inexpensively and simply producing α-L- aspartyl-L-phenylalanine methyl ester or α-L-aspartyl-L-phenylalanine from L-isoasparagin and L-phenylalanine methyl ester. SOLUTION: This method for producing the subject compound comprises reacting a microbial cell of a microorganism belonging to the genus Cedecea, Enterobacter, Escherichia, Hafnia, Klebsiella, Morganella, Rahnella, Serratia or Yersinia or a treated material of the cell with L-isoasparagin and L- phenylalanine methyl ester and collecting α-L-aspartyl-L-phenylalanine methyl ester or α-L-aspartyl-L-phenylalanine.